Involvement of cancer-derived EMT cells in the accumulation of 18F-fluorodeoxyglucose in the hypoxic cancer microenvironment - Sachi Sugita (Nature Portfolio, 2021)
Abstract A high rate of glycolysis, one of the most common features of cancer, is used in positron emission tomography (PET) imaging to visualize tumor tissues using 18F-fluorodeoxyglucose (18F-FDG). Heterogeneous intratumoral distribution of 18F-FDG in tissues has been established in some types of cancer, and the maximum standardized uptake value (SUVmax) has been correlated with poor prognosis. However, the phenotype of cells that show high 18F-FDG accumulation in tumors remains unknown. Here, we combined quantitative micro-autoradiography with fluorescence immunohistochemistry to simultaneously visualize 18F-FDG distribution, the expression of multiple proteins, and hypoxic regions in the cancer microenvironment of a human A431 xenograft tumor in C.B-17/Icr-scid/scid mice. We found that the highest 18F-FDG accumulation was in cancer-derived cells undergoing epithelial-mesenchymal transition (EMT) in hypoxic regions, implicating these regions as a major contributor to increased glucose metabolism, as measured by 18F-FDG-PET.